Reengineering the topological structure of large-scale monitoring systems - Beskorovainyi, V.; Podoliaka, K. (ECONTECHMOD, 2015)
As part of the solution of problem optimization of large-scale facilities carried out formalization of the system description of large-scale monitoring, defined the composition and the relationship subsets of elements, relationships, topologies and properties. Formulated the mathematical model and the task of reengineering topological structures of centralized three-tier system of largescale monitoring based on indices of cost and efficiency. The proposed mathematical model explicitly set relation between costs for the reengineering and time processing messages in the system from its structure and topology. The analysis of the objective function revealed that envelopes their local extrema are one-extreme (relative to the number of nodes in the system). Considering this, proposed a method of directed inspection of local extrema, which allow to find best solutions in terms of the minimum additional cost. Selection of the single solution from a set of effective proposed to carry out the method of hierarchy analysis or cardinalist approach aided by the additive function of general utility. The values of the weighting coefficients of the utility functions is carried out by an expert or based on comparator identification. Practical application these results allows reduce the time of obtaining solutions and more accurate solving of large dimension problem.
Keywords: large-scale monitoring system (LSMS); structure; topology; reengineering